Multi-age Alliances: Ethnographies of Children and Adults Against the Impoverishment of Life - Morano, Luisina (2025)
From an ethnographic approach, the article aims to study the intergenerational relationships established by children and adults in two distinct contexts: a peripheral and gentrified neighborhood of an agricultural locality in Buenos Aires province, and squatted houses located in a central neighborhood of Buenos Aires city. With a theoretical framework rooted in ontological feminisms and the anthropology of ages, the text analyzes the survival strategies developed jointly by different age groups, both within family networks and community settings. The results indicate that these intergenerational practices, beyond the economic aspect, are vital for enjoying life in contexts of increasing inequality and conservatism.